2019
DOI: 10.21608/ejaj.2019.52843
|View full text |Cite
|
Sign up to set email alerts
|

Plant Parasitic Nematodes Associated with Wheat in Northern and Middle Egypt

Abstract: Distribution and identification of phytonematodes associated with wheat grown in twelve provinces of Northern and Middle Egypt were investigated during two growing seasons (2016-2017 and 2017-2018). A total of 929 soil and root samples were collected from 119 localities (villages/farms) belonging to 37 districts. Samples contained fourteen nematode genera and species viz.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…were found to be the most prominent in wheat fields in Ismailia governorate (PV= 67.35 and 37.95, respectively). These results are in coincidence with those previously reported by Korayem et al (2019) who indicated that there were 14 nematode genera and species associating wheat plants in 12 governorates in northern and mid Egypt. They also concluded that Tylenchorhynchus spp., Pratylenchus spp., Helicotylenchus spp., and Heterodera app.…”
Section: Resultssupporting
confidence: 92%
“…were found to be the most prominent in wheat fields in Ismailia governorate (PV= 67.35 and 37.95, respectively). These results are in coincidence with those previously reported by Korayem et al (2019) who indicated that there were 14 nematode genera and species associating wheat plants in 12 governorates in northern and mid Egypt. They also concluded that Tylenchorhynchus spp., Pratylenchus spp., Helicotylenchus spp., and Heterodera app.…”
Section: Resultssupporting
confidence: 92%
“…Sikandar et al (2020) mentioned that P. chrysogenum (Snef1216) caused inhibition of the egg hatching and increased mortality of M. incognita, relying on increasing the concentration and exposure time to the fungus filtrate; as a novel nematicidal agent against the root-knot nematode. Korayem et al (2019) stated that Aspergillus spp., A. niger, Fusarium spp., Penicillium spp., and Trichoderma spp. were common fungi in the rhizosphere of wheat crop grown in different governorates of Egypt.…”
Section: Impact On Percentage Of Fungal Frequencymentioning
confidence: 99%